Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
2: =>2x-1/4=5/6-1/2x
=>5/2x=5/6+1/4=13/12
=>x=13/30
3: =>3x-5/6=2/3-1/2x
=>3,5x=2/3+5/6=4/6+5/6=9/6=3,2
hay x=32/35
a) \(\frac{1}{4}+\frac{3}{4}x=\frac{3}{4}\Leftrightarrow\frac{3}{4}x=\frac{1}{2}\Leftrightarrow x=\frac{1}{2}\times\frac{4}{3}\Leftrightarrow x=\frac{2}{3}\)
b)\(1\frac{3}{4}x+1\frac{1}{2}=-\frac{4}{5}\Leftrightarrow\frac{7}{4}x+\frac{3}{2}=-\frac{4}{5}\Leftrightarrow\frac{7}{4}x=-\frac{23}{10}\)
\(\Leftrightarrow x=-\frac{23}{10}\times\frac{4}{7}\Leftrightarrow x=-\frac{46}{35}\)
c)\(\frac{3}{4}x+\frac{2}{5}x=1,2\Leftrightarrow x\left(\frac{3}{4}+\frac{2}{5}\right)=1,2\Leftrightarrow\frac{23}{20}x=1,2\)
\(\Leftrightarrow x=1,2\times\frac{20}{23}\Leftrightarrow x=\frac{24}{23}\)
d)\(\frac{3}{7}+\frac{1}{7}:x=\frac{3}{14}\Leftrightarrow\frac{1}{7x}=\frac{3}{14}-\frac{3}{7}\Leftrightarrow\frac{1}{7x}=-\frac{3}{14}\Leftrightarrow14=-3\times7x\)
\(\Leftrightarrow-21x=14\Leftrightarrow x=-\frac{2}{3}\)
e) \(-\frac{3}{4}-\left|\frac{4}{5}-x\right|=-1\Leftrightarrow\left|\frac{4}{5}-x\right|=-\frac{3}{4}+1\Leftrightarrow\left|\frac{4}{5}-x\right|=\frac{1}{4}\)
\(\Leftrightarrow\left[{}\begin{matrix}\frac{4}{5}-x=\frac{1}{4}\\\frac{4}{5}-x=-\frac{1}{4}\end{matrix}\right.\)
\(\Leftrightarrow\left[{}\begin{matrix}x=\frac{11}{20}\\x=\frac{21}{20}\end{matrix}\right.\)
a, \(\frac{1}{4}+\frac{3}{4}x=\frac{3}{4}\\ \Rightarrow\frac{3}{4}x=\frac{1}{2}\\ \Rightarrow x=\frac{2}{3}\)
Vậy \(x=\frac{2}{3}\)
b, \(1\frac{3}{4}x+1\frac{1}{2}=\frac{-4}{5}\\ \frac{7}{4}x+\frac{3}{2}=\frac{-4}{5}\\ \Rightarrow\frac{7}{4}x=\frac{-23}{10}\\ \Rightarrow x=\frac{-46}{35}\)
Vậy \(x=\frac{-46}{35}\)
c, \(\frac{3}{4}x+\frac{2}{5}x=1,2\\ x\left(\frac{3}{4}+\frac{2}{5}\right)=\frac{6}{5}\\ x\cdot\frac{23}{20}=\frac{6}{5}\\ \Rightarrow x=\frac{24}{23}\)
Vậy \(x=\frac{24}{23}\)
d, \(\frac{3}{7}+\frac{1}{7}:x=\frac{3}{14}\\ \Rightarrow\frac{1}{7}:x=\frac{-3}{14}\\ \Rightarrow x=\frac{-2}{3}\)
Vậy \(x=\frac{-2}{3}\)
e, \(\frac{-3}{4}-\left|\frac{4}{5}-x\right|=-1\\ \Rightarrow\left|\frac{4}{5}-x\right|=\frac{1}{4}\\ \Rightarrow\left[{}\begin{matrix}\frac{4}{5}-x=\frac{1}{4}\\\frac{4}{5}-x=\frac{-1}{4}\end{matrix}\right.\Rightarrow\left[{}\begin{matrix}x=\frac{11}{20}\\x=\frac{21}{20}\end{matrix}\right.\)
Vậy \(x\in\left\{\frac{11}{20};\frac{21}{20}\right\}\)
a) \(\left|2x+\frac{3}{4}\right|=\frac{1}{2}\)
\(\orbr{\begin{cases}2x+\frac{3}{4}=\frac{1}{2}\\2x+\frac{3}{4}=\frac{-1}{2}\end{cases}}\) => \(\orbr{\begin{cases}2x=\frac{1}{2}-\frac{3}{4}\\2x=\frac{-1}{2}-\frac{3}{4}\end{cases}}\) => \(\orbr{\begin{cases}2x=\frac{-1}{4}\\2x=\frac{-5}{4}\end{cases}}\) => \(\orbr{\begin{cases}x=\frac{-1}{8}\\x=\frac{-5}{8}\end{cases}}\)
Vậy \(x=\left\{\frac{-1}{8},\frac{-5}{8}\right\}\)
b) \(\frac{3x}{2,7}=\frac{\frac{1}{4}}{2\frac{1}{4}}\)= \(\frac{3x}{2,7}=\frac{\frac{1}{4}}{\frac{9}{4}}\)
=> \(3x.\frac{9}{4}=2,7.\frac{1}{4}\)=> \(\frac{27x}{4}=\frac{27}{40}\)
\(27x.40=27.4\)
\(1080.x=108\)
\(x=\frac{1}{10}\)
Vậy \(x=\frac{1}{10}\)
c) \(\left|x-1\right|+4=6\)
\(\left|x-1\right|=6-4\)
\(\left|x-1\right|=2\)
\(\orbr{\begin{cases}x-1=2\\x-1=-2\end{cases}}\)=> \(\orbr{\begin{cases}x=3\\x=-1\end{cases}}\)
Vậy \(x=\left[3,-1\right]\)
d) \(\frac{x}{3}=\frac{y}{5}=>\frac{y}{5}=\frac{x}{3}=>\frac{y-x}{5-3}=\frac{24}{2}=12\)
e) \(\left(x^2-3\right)^2=16\)
\(\left(x^2-3\right)^2=4^2\)\(=>x^2-3=4\)
\(x^2=7=>x=\sqrt{7}\)
Vậy \(x=\sqrt{7}\)
f) \(\frac{3}{4}+\frac{2}{5}x=\frac{29}{60}\)
\(\frac{2}{5}x=\frac{29}{60}-\frac{3}{4}\)
\(\frac{2}{5}x=-\frac{4}{15}\)
\(x=-\frac{4}{15}:\frac{2}{5}=-\frac{4}{15}.\frac{5}{2}=-\frac{2}{3}\)
Vậy \(x=-\frac{2}{3}\)
g) \(\left(-\frac{1}{3}\right)^3.x=\frac{1}{81}\)
\(\left(-\frac{1}{27}\right).x=\frac{1}{81}\)
\(x=\left(-\frac{1}{27}\right):\frac{1}{81}=\left(-\frac{1}{27}\right).81=-3\)
Vậy \(x=-3\)
k)\(\frac{3}{4}-\frac{2}{5}x=\frac{29}{60}\)
\(\frac{2}{5}x=\frac{3}{4}-\frac{29}{60}\)
\(\frac{2}{5}x=\frac{4}{15}\)
\(x=\frac{2}{5}-\frac{4}{15}=>x=\frac{2}{15}\)
Vậy \(x=\frac{2}{15}\)
I) \(\frac{3}{5}x-\frac{1}{2}=-\frac{1}{7}\)
\(\frac{3}{5}x=-\frac{1}{7}+\frac{1}{2}\)
\(\frac{3}{5}x=\frac{5}{14}\)
\(x=\frac{5}{14}:\frac{3}{5}=\frac{5}{14}.\frac{5}{3}=\frac{25}{42}\)
Vậy \(x=\frac{25}{42}\)
\(\left|x+\frac{1}{3}\right|-4=-2\)
\(\left|x+\frac{1}{3}\right|=-2+4\)
\(\left|x+\frac{1}{3}\right|=2\)
\(\Rightarrow\orbr{\begin{cases}x+\frac{1}{3}=2\\x+\frac{1}{3}=-2\end{cases}\Leftrightarrow}\orbr{\begin{cases}x=2-\frac{1}{3}\\x=-2-\frac{1}{3}\end{cases}\Leftrightarrow\orbr{\begin{cases}x=\frac{5}{3}\\x=\frac{-7}{3}\end{cases}}}\)
\(|x+\frac{1}{3}|-4=-2\)
\(|x+\frac{1}{3}|=2\)
\(\Rightarrow\orbr{\begin{cases}x+\frac{1}{3}=2\\x+\frac{1}{3}=-2\end{cases}\Rightarrow\orbr{\begin{cases}x=\frac{5}{3}\\x=-\frac{7}{3}\end{cases}}}\)